Risk factor evaluation of cuff pressure of >30 cmH2O to stop air leakage during mechanical ventilation: A prospective observational study - Hong‐Lei Wu; Yue‐Hong Wu; Wang‐Qin Shen; Jia‐Hai Shi; Yan‐Ping Zhu; Yang‐Hui Xu; Hong‐Wu Shen; Lei Ding (Wiley, 2024)
Abstract Aim The commonly recommended endotracheal tube cuff pressure is 20-30 cmH2O. However, some patients require a cuff pressure of >30 cmH2O to prevent air leakage. The study aims to determine the risk factors that contribute to the endotracheal tube cuff pressure of >30 cmH2O to prevent air leakage. Design A multi‐centre prospective observational study. Methods Eligible patients undergoing mechanical ventilation in the intensive care unit of three hospitals between March 2020 and July 2022 were included. The endotracheal tube cuff pressure to prevent air leakage was determined using the minimal occlusive volume technique. The patient demographics and clinical information were collected. Results A total of 284 patients were included. Among these patients, 55 (19.37%) patients required a cuff pressure of >30 cmH2O to prevent air leakage. The multivariate logistic regression results revealed that the surgical operation (odds ratio [OR]: 8.485, 95% confidence interval [CI]: 1.066-67.525, p = 0.043) was inversely associated with the endotracheal tube cuff pressure of >30 cmH2O, while the oral intubation route (OR: 0.127, 95% CI: 0.022-0.750, p = 0.023) and cuff inner diameter minus tracheal area (OR: 0.949, 95% CI: 0.933-0.966, p < 0.001) were negatively associated with the endotracheal tube cuff pressure of >30 cmH2O. Therefore, a significant number of patients require an endotracheal tube cuff pressure of ＞30 cmH2O to prevent air leakage. Several factors, including the surgical operation, intubation route, and difference between the cuff inner diameter and tracheal area at the T3 vertebra, should be considered when determining the appropriate cuff pressure during mechanical ventilation.